Ultrasound-assisted fabrication of biodegradable and conductive PANI/sago/graphene hybrid nanocomposites for sustainable and flexible electronics - Mohammed E. Ali Mohsin; Suleiman Mousa; Sohail M.A.K. Mohammed; Agus Arsad (Polymer Testing, 2025)
The growing demand for high-performance portable electronic devices has intensified electromagnetic interference (EMI) pollution and electronic waste (e-waste), necessitating the development of sustainable conductive materials. This study introduces a novel ultrasound-assisted in situ oxidative polymerization method to fabricate polyaniline (PANI)/sago/graphene (PSG) hybrid nanocomposites. Morphological analyses (SEM and TEM) confirmed uniform dispersion of graphene nanoplatelets, spectroscopic studies (FTIR and UV–Vis) revealed enhanced molecular interactions, and thermal analysis (TGA) demonstrated superior thermal stability with a T50 of 497 °C. These interactions produced a low percolation threshold of 0.95 wt% GNP, a maximum DC conductivity of 3.44 × 10−1 S/cm, significantly surpassing that of PANI/Sago blend alone (2.17 × 10−3 S/cm). AC conductivity analysis revealed a broad plateau (102–106 Hz) via tunnelling and hopping mechanisms, with electrical performance retained up to 100 °C. These properties, combined with sago starch's biodegradability, position PSG nanocomposites as eco-friendly candidates for flexible electronics, EMI shielding, and biodegradable transient devices.